Concentrations and distributions of polybrominated diphenyl ethers and novel brominated flame retardants in tree bark and human hair from Yunnan Province, China. (July 2016) - Yuan, Haodong; Jin, Jun; Bai, Yao; Li, Qiuxu; Wang, Ying; Hu, Jicheng
Abstract: The concentrations and distributions of polybrominated diphenyl ethers (PBDEs) and novel brominated flame retardants (NBFRs) in tree bark and hair samples from the same area in Yunnan Province, China, were determined. The total PBDE and NBFR concentrations in the tree bark samples were 3.8 ng/g lipid weight to 91 ng/g lipid weight and 0.23 ng/g lipid weight to 5.0 ng/g lipid weight, respectively. The total PBDE and NBFR concentrations in the hair samples were 2.1 ng/g dry weight to 14 ng/g dry weight and 0.083 ng/g dry weight to 0.29 ng/g dry weight, respectively. Decabromodiphenyl ether had similar distributions in the tree bark and hair samples, but other PBDE congeners and NBFRs had different distributions in the tree bark and hair samples. External exposure was found to be mainly responsible for the total PBDE and pentabromotoluene concentrations in hair, but both external and internal exposure were responsible for the pentabromophenyl and hexabromobenzene concentrations in hair. Graphical abstract: Highlights: Associations between BFR concentrations in tree bark and hair samples from inhabitants of the same areas were found. BDE-209 was found to be the source of lower BDE congeners. External exposure was found to be the main factor for BDE-209 and PBT concentration in hair.